FAKTOR RISIKO SINDROM METABOLIK PADA ORANG DEWASA DI KOTA BOGOR - Marice Sihombing; Dwi Hapsari Tjandrarini (Persagi, 2015)
ABSTRACTMetabolic syndrome (MS) is a group of disorders metabolism that are associated with increased risk of cardiovascular disease. The aims of this study was to determined risk factors of MS among adults in Bogor.Baseline data of Cohort Study on Non Communicable Disease in Bogor during the year 2011 to 2012 was used for data analysis. Of the total 5290 records, 4644 participants aged 25-65 year matched the inclusion criteria for analysis. Demographic and lifestyle data were collected using structured questionair. Physical examination (included weight, height, waist circumference, and blood pressure) and laboratory indicators (fasting glucose, HDL cholesterol, and triglyserides) were performed. Diagnosis of MS based of the criteria of The National Cholesterol Education Programme Adult Treatment Panel III (NCEP ATP III) for Asian population. Resultsshowed overall proportion of MS was 18.2 per cent (14.2% in men, and 20.2% in women). Participants in aged group of 35 to 44 years had risk 1.84 time (CI 1.37-2.50, p= 0.000) for MS compared to participants in aged group of 25 to 34 years. Participants in the older aged groups (45-54 y and 55-65 y) had risk 3,34 and 4 times respectively. Participants with obese got risk 7.5 times compared with non obes. Participants who took fried meals was risk 1.21 times. The proportion of components of MS more higher among women than men and the proportion of component of central obesity is dominant. The determinant factors were aged, obese andconsumed fried meals. The risk for MS increased with the aged of the participants.Keywords: central obesity, physical examination, laboratory indicatorsABSTRAKSindrom metabolik (SM) merupakan kumpulan gangguan metabolisme yang dikaitkan dengan peningkatan risiko penyakit kardiovaskuler. Tujuan analisis ini adalah menentukan faktor risiko SM pada orang dewasa diKota Bogor. Analisis menggunakan data dasar ‘Studi Kohor Faktor Risiko Penyakit Tidak Menular’ tahun 2011 sampai dengan 2012. Sebanyak 4644 dari 5290 partisipan berumur antara 25 dan 65 tahun memenuhikriteria untuk dianalisis. Data yang telah dikumpulkan berupa data demografi dan perilaku/gaya hidup; pemeriksaan fisik (pengukuran berat badan, tinggi badan, lingkar perut, dan tekanan darah), pemeriksaanlaboratorium (gula darah puasa, kolesterol HDL, dan trigliserida). Diagnosis SM menggunakan kriteria the national cholesterol education programme adult treatment panel III (NCEP-ATP III) untuk orang Asia. Hasil analisis menunjukkan bahwa berdasarkan kriteria NCEP-ATP III, ditemukan proporsi SM sebesar 18,2 persen (laki laki 14,2% dan perempuan 20,2%). Partisipan kelompok umur 35-44 tahun berisiko 1,84 kali (CI 1,37-2,50, p=0,000) untuk mendapat SM dibandingkan pada kelompok umur 25-34 tahun. Partisipan kelompok umur yang lebih tua yaitu 45-54 tahun dan 55-65 tahun masing-masing berisiko 3,34 kali dan 4 kali. Risiko mendapat SM bagi penderita obesitas sebesar 7,5 kali; pengonsumsi jajanan gorengan sebesar 1,21 kali. Proporsi komponen SM lebih tinggi pada perempuan dibandingkan dengan laki laki; dan komponen yang paling dominan adalah obesitas sentral (87,5%). Faktor determinan terjadinya SM pada orang dewasa adalah umur, obesitas, dan sering mengonsumsi jajanan gorengan. Risiko SM meningkat seiring dengan bertambahnya umur partisipan. [Penel Gizi Makan 2015, 38(1): 21-30].Kata kunci: obesitas sentral, pemeriksaan fisik, indikator laboratorium